Interaction of Carbon Nanotubes, Capped Carbon Nanotubes, CNT2–5, C60, C70, HO-C60, [C60]2, and [C60]3 Fullerenes with Virulence Factors of Gram-Negative and Gram-Positive Bacteria: Potential Applications for 3D-Printed Scaffolds - Mehran Alavi; Morahem Ashengroph; M. R. Mozafari (Inorganics, 2024)
The antimicrobial application of carbon nanomaterials, such as carbon nanotubes (CNTs), capped CNTs, CNT2–5, C60, C70, HO-C60, [C60]2, and [C60]3 fullerenes, is increasing, owing to their low cytotoxicity properties compared to other nanomaterials such as metallic nanoparticles. Enhanced mechanical properties and antibacterial activity can be caused by the incorporation of CNTs in 3-dimensional (3D) printed nanocomposites (NCs). The interruption of the bacterial membrane resulting from the cylindrical shape and high aspect ratio properties has been found to be the most prominent antibacterial mechanism of CNTs. However, the unraveling interaction of CNTs, capped CNTs, CNT2–5, C60, C70, HO-C60, [C60]2, and [C60]3 fullerenes with virulence factors of the main bacterial pathogenesis has not yet been understood. Therefore, in the present study, interactions of these carbon-based nanomaterials with the eight virulence factors, including protein kinase A and (ESX)-secreted protein B of Mycobacterium tuberculosis, pseudomonas elastase and exotoxin A of Pseudomonas aeruginosa, alpha-hemolysin and penicillin-binding protein 2a of Staphylococcus aureus, and shiga toxin 2a and heat-labile enterotoxin of Escherichia coli, were evaluated with the molecular docking method of AutoDock Vina. This study disclosed that the binding affinity was highest for CNT2–5 and [C60]3 toward alpha-hemolysin, with binding energies of −32.7 and −26.6 kcal/mol, respectively. The stability of the CNT2–5–alpha-hemolysin complex at different times was obtained according to the normal mode analysis of ElNémo and iMOD servers.